Analyzing barriers to the effective implementation of technological tools in inclusive education: a scoping review - Murillo-Jiménez, Humberto; Centeno-Alarcón, Marco; Buele, Jorge; Yumbla, Francisco (Frontiers in Education, 2025)
IntroductionDigital accessibility and inclusive pedagogy are central to achieving equitable education systems worldwide. Yet, the integration of technological tools for students with disabilities remains inconsistent, often limited to fragmented initiatives without long-term institutional or policy support. Understanding the structural barriers that constrain digital inclusion is crucial for transforming technology into an enabler of educational equity rather than a source of further exclusion.MethodsThis study conducted a scoping review following PRISMA-ScR guidelines to identify and analyze barriers affecting the implementation of educational technologies in inclusive education. A systematic search across six databases (ERIC, Scopus, ACM Digital Library, EBSCOhost, Wiley Online Library, and Web of Science) yielded nine primary studies published between 2015 and 2025. Data were thematically synthesized through inductive–deductive coding to identify recurring structural, pedagogical, and policy patterns.ResultsThe findings reveal persistent deficits in teacher training and digital competence, technological and infrastructural limitations, economic constraints, and weak enforcement of inclusion policies. Additionally, attitudinal barriers, including low expectations toward students with disabilities and limited institutional accountability, hinder sustainable progress. Positive factors, such as teacher initiative, institutional commitment, and universal design-based practices, partially mitigate these challenges, demonstrating the potential of inclusive technologies when supported by coherent policy and training structures.ConclusionEnsuring genuine digital inclusion requires embedding accessibility and universal design as structural components of education systems. Sustainable progress depends on coordinated governance, investment, and professional development that bridge the gap between policy and classroom practice.RegistrationThis review was registered in Open Science Framework: 10.17605/OSF.IO/T5K7Y.